The Gender Equality in CLIS Model and Brain Gym Technique: A Review of Cognitive Learning Outcomes - Sele, Yunawati; Nomleni, Fransina Th; Sir, Mega Selviana (Unnes Science Education Journal, 2021)
Gender equality is one of the important topics that need attention in learning. This study aims at finding out the cognitive learning outcomes of the equality of male and female students in Children Learning in Science (CLIS) that was combined with a Brain Gym. This study is a a comparative research. The population of this study were the students of grade XI MIA SMA Negeri 7 Kupang in the academic year of 2018/2019 and the sample of this study were the students of grade XI MIA 1. The instrument used was a test of cognitive learning outcomes. The data obtained were analyzed using Anakova. The results showed that by combining CLIS and Brain Gym technique, the equality of cognitive learning outcomes for male and female students can occur. Providing the same opportunities, the same tasks, and the same responsibilities during CLIS combined with a Brain Gym learning, can minimize the differences in characteristics between genders so that the learning outcomes obtained are equivalent.